PERKAWINAN ANAK DI BAWAH UMUR TANPA IZIN ORANG TUA MENURUT FIQIH ISLAM, KOMPILASI HUKUM ISLAM DAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - EVY SUSANTY (PREMISE LAW JURNAL, 2015)
The conclusion is that, first, in Islamic Fiqh, Islamic Law Compilation, and Law on Marriage, the marriage of minors without parental permission is not allowed. According to Islamic Fiqh and Islamic Law Compilation, legal consequence of the marriage of minors without parental permission is illegal or canceled. According to Law No.1/1974 on Marriage, legal consequence of the marriage of minors without parental permission is the marriage can be canceled. The significant difference found in Islamic Fiqh and Islamic Law Compilation, and Law on Marriage is in the aspects of the determination of age limit to get married and prental permission. It is suggested that, first, Article 2 paragraph (1) of Law on Marriage be an important guidance for those who are going to get married; second, to avoid the consequences resulted from the marriage of minors without parental persmission, the prevention efforts should be done before the marriage occurs or the cancellation efforts should be done if the marriage has already carried out; and third, the age limit to get married in the Islamic Law Compilation and Law on Marriage must be changed into minimum 18 (eighteen) years old without distinguising the age of man and woman. This age limit can, at least, meet the minimum age limit of 20 (twenty) years old according to the Convention of Child Rights, because this age is the most eligible condition of biological and psychological maturity Keywords: Marriage of Minors Without Parental Permission, Islamic Fiqh, Islamic Law Compilation, Law on Marriage